Canadian Identity and Curriculum Theory: An Ecological, Postmodern Perspective - Sumara, Dennis; Davis, Brent; Laidlaw, Linda (Canadian Journal of Education/Revue canadienne de l’éducation, 2001)
In this article, we develop the thesis that curriculum studies work in Canada might be characterized in terms of some persistent and consistent theoretical commitments, ones that we suggest might have been prompted in part by the nation’s history and by popular commentaries on national identity. We draw on ecological and postmodern discourses in efforts to conceptualize and to describe a relationship between Canadian culture(s) and the development of theories of curriculum within the Canadian context. Cet article avance l’hypothèse que les études du curriculum au Canada peuvent être vues comme des engagements continus et cohérents qui ont été en partie suscités par l’histoire du pays et des idées courantes sur l’identité nationale. Les auteurs s’inspirent de discours écologiques et postmodernes en vue d’établir un lien entre les cultures canadiennes et le développement de théories du curriculum dans le contexte canadien.